2020
DOI: 10.1002/jbt.22470
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of allicin against acetaminophen‐induced liver injury: Role of inflammasome pathway, apoptosis, and liver regeneration

Abstract: Acetaminophen (APAP) overdose leads to liver injury. NLRP3 inflammasome is a key player in APAP-induced inflammation. Also, apoptosis and liver regeneration play an important role in liver injury. Therefore, we assessed allicin's protective effect on APAP-induced hepatotoxicity and studied its effect on NLRP3 inflammasome and apoptosis. Mice in the APAP group were injected by APAP (250 mg/kg, intraperitoneal). The allicin-treated group received allicin orally (10 mg/kg/d) during 7 days before APAP injection. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Although the time course of APAP-induced hepatotoxicity as well as the role of inflammasome in the process have been extensively investigated, the relationship between necroptosis and inflammasome remains largely unknown. 25,37,38 To further testify the mechanistic linkage between necroptosis and NLRP3 inflammasome in APAP liver injury, we next examined whether the necroptosis-inhibiting drug could reduce the upregulation of NLRP3 inflammasome Figure 7. Nec-1 treatment inhibited the activation of NLRP3 inflammasome signaling pathway in liver tissues of C57BL/6 mice following APAP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the time course of APAP-induced hepatotoxicity as well as the role of inflammasome in the process have been extensively investigated, the relationship between necroptosis and inflammasome remains largely unknown. 25,37,38 To further testify the mechanistic linkage between necroptosis and NLRP3 inflammasome in APAP liver injury, we next examined whether the necroptosis-inhibiting drug could reduce the upregulation of NLRP3 inflammasome Figure 7. Nec-1 treatment inhibited the activation of NLRP3 inflammasome signaling pathway in liver tissues of C57BL/6 mice following APAP administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, acetaminophen overdose is the most frequent cause of acute liver failure in the United States and many European countries (Larson et al, 2005;Yano et al, 2014). Severe liver injury, along with increasing expressions of NLRP3 and IL-1β, occurred in acetaminophen-treated mice liver or liver cell lines Lv et al, 2020;Samra et al, 2020;Shi et al, 2020). Imaeda et al (2009) found that genetic deficiencies in NLRP3 inflammasome components (NLRP3, ASC, and caspase-1) provided protection from acetaminophen-induced mice death and liver injury.…”
Section: Acetaminophen-induced Liver Injurymentioning
confidence: 99%
“…Similarly. Allicin (an active sulfur species isolated from garlic) also protected the mouse liver from acetaminopheninduced necrosis, apoptosis, and hepatocellular degeneration via inhibiting the hepatic NLRP3 inflammasome activation and IL-1β secretion and increasing Ki-67 level (Samra et al, 2020).…”
Section: Phytochemicals That Treat Drug-induced Liver Injurymentioning
confidence: 99%
“…Intercellular contents released from these damaged cells, called damage-associated molecular patterns (DAMPs), which can stimulate nonparenchymal cells to produce and release in ammatory mediators and chemokines [12]. Under the action of chemokines, a variety of immune and in ammatory cells, such as monocytes and neutrophils, are recruited into the liver and promote in ammatory responses via the activation of innate immune signal transduction pathways, resulting in the necrosis and apoptosis of liver cells [13]. Importantly, blocking oxidative stress and inhibiting in ammation are important targets for protecting hepatocytes from hepatotoxicity of APAP.…”
Section: Introductionmentioning
confidence: 99%